Secondary World in Fantasy Tradition after J. K. Rowling - Nemickienė, Živilė; Vengalienė , Dovilė (Respectus Philologicus, 2023)
The aim is to evaluate Rowling’s world of fairy tales and its adherence to the criteria of a fantasy secondary world according to the frameworks proposed by T. Todorov (1973), R. Jackson (1981), and F. Mendlesohn (2008). The secondary world in the Harry Potter series, the wizarding world, is open to the real world and shares its geography, yet hidden from non-magical people. It is consistently described with its own culture, customs, traditions, and social norms. The central conflict is between Good and Evil for domination, with Evil aiming to extend its power to both the magic world and the real world. The fantasy world is relatable to readers due to its handling of universal themes and issues relevant to their lives, transferring characters into new life conditions. Research methods include content analysis, psychological research, and comparative analysis.
Keywords: secondary world; psychological accuracy; dichotomous time; fantasy; determinacy